Trajectoires résidentielles et stratégies de recomposition spatiale face aux risques littoraux - Jeanne Dachary-Bernard; Sandrine Lyser; Didier Vye (Développement Durable et Territoires)
In the face of climate change, the implementation of risk adaptation strategies in coastal areas is receiving a growing interest, particularly from land managers. Managed retreat, or spatial reorganisation, involves a planned move of goods and people to non-vulnerable areas. This article examines the role played by households' residential pathways in their propensity to plan a retreat by 2040. Based on a survey carried out on the Landes coast (Capbreton), we emphasize the importance of identifying the main dimensions of these residential pathways in order to co-construct relocation strategies with the population.